2004
DOI: 10.1111/j.1462-2920.2004.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maize mucilage on the diversity and activity of the denitrifying community

Abstract: In order to understand the effect of the maize rhizosphere on denitrification, the diversity and the activity of the denitrifying community were studied in soil amended with maize mucilage. Diversity of the denitrifying community was investigated by polymerase chain reaction (PCR) amplification of total community DNA extracted from soils using gene fragments, encoding the nitrate reductase (narG) and the nitrous oxide reductase (nosZ), as molecular markers. To assess the underlying diversity, PCR products were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 39 publications
3
62
1
Order By: Relevance
“…This cluster was comprised of narG sequences from Hythe and Alresford sediments only. A further 10 clones (cluster II) were most closely related to narG sequences derived from agricultural soils (11,41). Four clones were related to narG sequences derived from agricultural soils (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This cluster was comprised of narG sequences from Hythe and Alresford sediments only. A further 10 clones (cluster II) were most closely related to narG sequences derived from agricultural soils (11,41). Four clones were related to narG sequences derived from agricultural soils (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar nosZ clones have also been obtained from other paddy fields (for example, GenBank Accession No. ACI48848) and maize rhizospheric soils (Mounier et al, 2004;Dambreville et al, 2006;Henry et al, 2008). Considering the general agreement between the 16S rRNA gene and nosZ phylogenies (Jones et al, 2008;Palmer et al, 2009), these results suggested that Herbaspirillum and other Burkholderiales bacteria may be important players in N 2 O reduction, not only in rice paddy soils but also in other environments.…”
Section: Discussionmentioning
confidence: 99%
“…The second cluster encompassed (1,9). Although several authors reported the diversity of the N 2 O-reducing community (10,18,23,24,28), no studies were performed to estimate its actual density. The isolation and characterization of denitrifiers based on their N 2 O-reducing abilities (2) are hampered by cultivation-dependent bias and the extensive manual effort due to the fact that denitrifiers represent a low percentage of the total FIG.…”
Section: Resultsmentioning
confidence: 99%